How bad is the Ukraine war for the European recovery? - European Investment Bank (2022)
"Before the war, the European economy was experiencing a heady recovery. The one-two punch of higher energy prices and trade disruptions, however, could destabilise EU firms already weakened by the pandemic, according to a new report published by the European Investment Bank. Simulations by the European Investment Bank find that the share of EU firms losing in money could rise, particularly among businesses hit by lower exports to Ukraine, Russia and Belarus and those exposed to higher energy prices. At the same time, rising inflation could push more Europeans under the poverty line."